"Strengthening Islamic Faith: Analysing Syekh Nawawi Al-Jawi's Contribution to Ahlussunnah Wal Jama'ah Belief in Indonesian Society through Aqidah, Shariah, and Morals" - firdaus, H muhammad; Fitriana, Fitriana (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
محاولة تأصيلية لمذهب أهل السنة والجماعة في مؤلفات الشيخ نووي الجاويوتفسيره نموذجامحمد فردوس*، فطريانا رشاي علي **muhammad.firdaus@uinjkt.ac.id*fitriana@uinjkt.ac.id** *المحاضر بالدراسات العليا قسم إدارة الدعوة بالجامعة الإسلامية الحكومية الشريف هدايات الله جاكرتا** المحاضر بالدراسات العليا قسم علوم القرآن والتفسير بالجامعة الإسلامية الحكومية الشريف هدايات الله جاكرتا   ملخص البحث  يحاول هذا البحث بصورته المتواضع التعرف على مدى التزام الشعب الإندونيسي بعقيدة أهل السنة والجماعة، وعلى وجه الخصوص مثابرة الشيخ نووي الجاوي في احتراسه ما ذهب إليه أهل السنة والجماعة في عدة المسائل، عقيدة وشريعة وأخلاقا. المشكلة التي يواجهها الباحث هي البحث عن  أقوال الشيخ نووي الجاوي التي تشير إلى اهتمامه بالمباحث العقلية ردا على الفرق المخالفة كالخوارج، والمعتزلة، والجهمية، وأهل الكلام، والفلاسفة، وذلك بتتبع ما شرح إليه الشيخ نووي الجاوي في مؤلفاته. تهدف هذه الدراسة إلى تحقيق ما جعل الشيخ نووي الجاوي رائده في ترسيخ منهاجه العقدي وتحليلاته العقلية في بلورة الأصول الإيمانية عند أهل السنة والجماعة. المنهج المتبع في هذه الدراسة هو المنهج الموضوعي، ويتم ذلك من خلال تتبع أقول الشيخ نووي الجاوي، وما لاحظ عليها العلماء والخبراء، مع الاستعانة بالمراجع الحديثة الأخرى من كتب التفاسير والأحاديث واللغة وغيرها. البحث منقسم إلى ثلاثة مطالب، المطلب الأول: المنهج الإجمالي لأهل السنة والجماعة في مؤلفات الشيخ نووي الجاوي. المطلب الثاني: موقف الشيخ نووي الجاوي من المباحث العقلية. المطلب الثالث: الخاتمة وأهم النتائج والتوصيات. "Strengthening Islamic Faith: Analysing Syekh Nawawi Al-Jawi's Contribution to Ahlussunnah Wal Jama'ah Belief in Indonesian Society through Aqidah, Shariah, and Morals"  AbstractThis study explains the extent of the Indonesian people's commitment to the ahlussunnah wal jama'ah belief, significantly the persistence of Syekh Nawawi Al-Jawi in maintaining the understanding of ahlussunnah wal jama'ah in case studies related to aqidah, shari'ah and morals. The background of the problem the author faces is examining the words of Sheikh Nawawi Al-Jawi, who shows his concern for theology in explaining the deviations committed by the Khawarij, Mu'tazilah, Jahmiyyah, theologians and philosophers by quoting the information presented by the Sheikh. Nawawi Al-Jawi in his books. This research aims to realise what has been pioneered by Syekh Nawawi Al-Jawi in strengthening the Islamic faith in Indonesian society -formerly until now- regarding theology which can be understood rationally through the method of studying the science of Kalam which is by the understanding of ahlussunnah wal jama'ah. The method used in this study is the thematic method, by observing the words of Sheikh Nawawi Al-Jawi and what the competent scholars pay attention to in the field of kalam by including other modern references from books of interpretation, hadith, language and others. This research is divided into three parts; the first part: a global explanation regarding ahlussunnah wal jama'ah in books written by Syekh Nawawi al-Jawi. The second part: the views and attitudes of Sheikh Nawawi Al-Jawi in discussing the science of kalam. Third part: conclusion. Keywords: Ahlussunnah Wal Jama'ah belief, aqidah, morals, Indonesian society, Islamic faith, science of Kalam, shariah, Syekh Nawawi Al-Jawi, theology deviations.